Histone deacetylases in cardiovascular and metabolic diseases. (May 2019) - Bagchi, Rushita A.; Weeks, Kate L.
Abstract: Histone deacetylases (HDACs) regulate gene transcription by catalyzing the removal of acetyl groups from key lysine residues in nucleosomal histones and via the recruitment of other epigenetic regulators to DNA promoter/enhancer regions. Over the past two decades, HDACs have been implicated in multiple processes pertinent to cardiovascular and metabolic diseases, including cardiac hypertrophy and remodeling, fibrosis, calcium handling, inflammation and energy metabolism. The development of small molecule HDAC inhibitors and genetically modified loss- and gain-of-function mouse models has allowed interrogation of the roles of specific HDAC isoforms in these processes. Isoform-selective HDAC inhibitors may prove to be powerful therapeutic agents for the treatment of cardiovascular diseases, obesity and diabetes.